The Role of Virtual Reality in Improving Pronunciation and Fluency in English Language Teaching - Gumarpi Rahis Pasaribu; Febrika Dwi Lestari; Muchlas Suseno (Asshika: Journal of English Language Teaching and Learning, 2024)
This study explores the effect of using Virtual Reality (VR) technology in improving pronunciation and fluency in learning English as a foreign language (EFL). By offering an immersive and interactive learning environment, VR allows learners to practice speaking skills in situations that mimic real-world conversations, potentially reducing anxiety and increasing confidence. This study identifies the role of VR in facilitating repeated exposure to accurate pronunciation models and assisting in developing speaking fluency through interactive simulation. The study's results indicate that using VR proves effective med primarily by providing action in a non-stressful environment. However, although VR shows positive results, its effectiveness in the long term and in a more realistic classroom context still requires further research. Also, it highlights the need for more in-depth studies on the comparison between training using VR and traditional methods, as well as the influence of individual factors such as anxiety and previous pronunciation training on learning outcomes.